Editor de textos - Garbin, Enio Antonio (1973)
Text editing or text composition is a technique to produce printed texts that has been growing steadily those last years. This growing is largely due to the increasing cost of man-power, the facility of using computers through time-sharing networks and the decreasing price of hardware. This work surveys and analizes the various text editors existing, establishes the main-points in the project of such systems and defines and implement one that follows those points, named independency, flexibility, universality, operability and safety.